2022
DOI: 10.3390/ijms23179565
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between the Chd4/NuRD Complex and the Transcription Factor Znf219 Controls Cardiac Cell Identity

Abstract: The sarcomere regulates striated muscle contraction. This structure is composed of several myofibril proteins, isoforms of which are encoded by genes specific to either the heart or skeletal muscle. The chromatin remodeler complex Chd4/NuRD regulates the transcriptional expression of these specific sarcomeric programs by repressing genes of the skeletal muscle sarcomere in the heart. Aberrant expression of skeletal muscle genes induced by the loss of Chd4 in the heart leads to sudden death due to defects in ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In mammals, the NuRD complex is approximately 1 MDa and comprises at least six to seven proteins, which generally exist as two or more paralogs: CHD4 (and its paralogues CHD3 and CHD5), MTA1 (plus MTA2 and MTA3), HDAC1 (and HDAC2), GATAD2A (and GATAD2B), MBD3 (and MBD2), RBBP4 (and RBBP7), and CDK2AP1 ( Low et al., 2016 ). Physical interaction between CHD4 and ZNF219 has been reported in cardiac tissues ( El Abdellaoui-Soussi et al., 2022 ). Recently, we found that the host protein TRIM28 is enriched in the PFV 5’LTR promoter region and positively regulates H3K9me3 marks ( Yuan et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, the NuRD complex is approximately 1 MDa and comprises at least six to seven proteins, which generally exist as two or more paralogs: CHD4 (and its paralogues CHD3 and CHD5), MTA1 (plus MTA2 and MTA3), HDAC1 (and HDAC2), GATAD2A (and GATAD2B), MBD3 (and MBD2), RBBP4 (and RBBP7), and CDK2AP1 ( Low et al., 2016 ). Physical interaction between CHD4 and ZNF219 has been reported in cardiac tissues ( El Abdellaoui-Soussi et al., 2022 ). Recently, we found that the host protein TRIM28 is enriched in the PFV 5’LTR promoter region and positively regulates H3K9me3 marks ( Yuan et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-Mi2 autoantibodies recognise chromodomain helicase DNA-binding (CHD) proteins, a family of ATP-dependent chromatin remodelers that are functionally critical subunits of the nucleosome remodelling and deacetylase (CHD4/NuRD) complex, a well-described transcriptional repressor 9 10. Although CHD3 and CHD4 are the most common target antigens tested in anti-Mi2 serological assays, CHD3 , CHD4 and CHD5 share significant sequence homology and are likely recognised by autoantibodies in anti-Mi2-positive DM patients.…”
Section: Introductionmentioning
confidence: 99%